Severe hypokalaemia in diabetic ketoacidosis: a contributor to central pontine myelinolysis?. (30th May 2019) - Chinoy, A; Wright, N B; Bone, M; Padidela, R
Summary: Hypokalaemia at presentation of diabetic ketoacidosis is uncommon as insulin deficiency and metabolic acidosis shifts potassium extracellularly. However, hypokalaemia is a recognised complication of the management of diabetic ketoacidosis as insulin administration and correction of metabolic acidosis shifts potassium intracellularly. We describe the case of a 9-year-old girl with newly diagnosed type 1 diabetes mellitus presenting in diabetic ketoacidosis, with severe hypokalaemia at presentation due to severe and prolonged emesis. After commencing management for her diabetic ketoacidosis, her serum sodium and osmolality increased rapidly. However, despite maximal potassium concentrations running through peripheral access, and multiple intravenous potassium 'corrections', her hypokalaemia persisted. Seventy two hours after presentation, she became drowsy and confused, with imaging demonstrating central pontine myelinolysis – a rare entity seldom seen in diabetic ketoacidosis management in children despite rapid shifts in serum sodium and osmolality. We review the literature associating central pontine myelinolysis with hypokalaemia and hypothesise as to how the hypokalaemia may have contributed to the development of central pontine myelinolysis. We also recommend an approach to the management of a child in diabetic ketoacidosis with hypokalaemia at presentation. Learning points: Hypokalaemia is a recognised complication of treatment of paediatric diabetic ketoacidosis that should be aggressively managed to prevent acute complications. Central pontine myelinolysis is rare in children, and usually observed in the presence of rapid correction of hyponatraemia. However, there is observational evidence of an association between hypokalaemia and central pontine myelinolysis, potentially by priming the endothelial cell membrane to injury by lesser fluctuations in osmotic pressure. Consider central pontine myelinolysis as a complication of the management of paediatric diabetic ketoacidosis in the presence of relevant symptoms with profound hypokalaemia and/or fluctuations in serum sodium levels. We have suggested an approach to the management strategies of hypokalaemia in paediatric diabetic ketoacidosis which includes oral potassium supplements if tolerated, minimising the duration and the rate of insulin infusion and increasing the concentration of potassium intravenously (via central line if necessary).